2022
DOI: 10.3389/fpls.2022.905738
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Enhancement for the Improvement of Castor Bean Growth and Yield, and Sustainable Biodiesel Production

Abstract: Due to limited conventional energy sources, there is a need to find substitute non-conventional sources of energy to meet the societal demands on a sustainable basis. Crude oil and edible oil remain major import items in Pakistan, the deficit of which can be compensated by using biomass, preferably inedible oilseeds. Therefore, the current study evaluated the role of sulfur (S) fertilization for improving yield (seed and oil) and biodiesel value of castor bean, a potential inedible crop with minimum input requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…In general, castor inflorescence type can impact seed purity and yield [9,10]. There are three types of castor inflorescence: MI, SFI, and BI (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In general, castor inflorescence type can impact seed purity and yield [9,10]. There are three types of castor inflorescence: MI, SFI, and BI (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There has been great incentive for castor production in Brazil and other countries in recent years, with intention mainly towards the production of biodiesel [ [6] , [7] , [8] , [9] ]. Due to these interests, some cultivars adapted for mechanized cultivation under crop rotation systems were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cultivating non-conventional oilseeds on marginal soils is practical, as it minimizes competition with food crops and helps alleviate the indirect effects of biofuel production on land use [9]. A recent study by Mukhtar, et al [17] indicated that non-edible oilseed species like castor bean (Ricinus communis) can yield stability even on marginal lands due to their tolerance to water stress, low soil fertility, high soil pH, and arid conditions. Similarly, Ramos, et al [5] observed that non-edible crops can be grown on lands unsuitable for arable crops, with lower water and fertilizer requirements, thus enhancing their economic viability.…”
Section: Introduction 1the Oil Seed Speciesmentioning
confidence: 99%
“…Such resources present promising and eco-friendly alternatives for enhancing biofuel characteristics through new and advanced technologies [18]. These non-edible oils offer advantages as diesel fuels due to their liquid nature, portability, ready availability, renewability, higher combustion efficiency, lower sulfur and aromatic content, and increased biodegradability [17,18]. Additionally, they can thrive in various climatic conditions [18].…”
Section: Introduction 1the Oil Seed Speciesmentioning
confidence: 99%